Water footprint messure method for tilapia, cachama and trout production: study cases to Valle del Cauca (Colombia) (2017)
(Eng) The pisciculture sector in Colombia, has grown 13% annually between 1988 and 2013, and it is the sixth major water user. Considering the influence that pisciculture has over the water resources, the water footprint of pisciculture was studied as a sustainability indicator, a method was developed to estimate the water footprint of the sector, which include not only the direct and indirect components, but also the green, blue and grey water footprint. The method was applied to the three most produced species in the country: tilapia (Oreochromis mossambicus), cachama (Piaractus brachypomus) and trout (Oncorhynchus mykiss), to corresponding case studies in Valle del Cauca, Colombia. It was found that the water footprint of tilapia culture is 5,486 m3/Ton, cachama culture is 6,193 m3/Ton, and trout culture is 19,854 m3/Ton. The highest total water footprint for tilapia was that of the concentrated feed, followed by the blue water footprint, associated with the amount of water that remains stored in the ponds, whereas for the cachama and trout, the highest water footprint was grey, due to the high concentrations of solids and nutrients present in fish excretions and unconsumed feed.